Analisis Kebutuhan Penggunaan Multimedia Interaktif Berbasis Discovery Learning Terhadap Kemampuan Berpikir Tingkat Tinggi Siswa dalam Pembelajaran IPA di SD - Miftahsus Silmi Zohro; Rafhi Febryan Putera; Neti Ramayani; Adinda Asri Ramadhanti (LP4MK STKIP PGRI Lubuklinggau, 2026)
This article aims to provide an overview of the benefits of interactive multimedia based on Discovery Learning in science education. One of the main problems in current science learning is the lack of students’ understanding, as science learning tends to be abstract and often leads students to memorize rather than comprehend concepts. This situation results in students’ limited skills in analyzing, problem-solving, and applying the concepts they have learned. This study employs a qualitative descriptive approach, with data collected through observations and interviews using relevant instruments. Based on the results of the needs analysis, it can be concluded that to create active and effective learning, the use of interactive multimedia based on Discovery Learning should be implemented. The use of this multimedia allows students to analyze, evaluate, and actively engage in learning activities, enabling them to discover concepts independently.